Attachment in Children: Determinants and Developmental Impacts: A Systematic Literature Review - Evanson Sakul, Bryan; Widyorini, Endang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This study emerges from growing concern over the quality of early child–caregiver relationships amid rapid social transformation, including shifting family structures, increased parental work demands, and the pervasive presence of digital technology, all of which reshape interaction patterns and potentially weaken the emotional foundations of Attachment. Accordingly, the study aims to develop a comprehensive and integrative understanding of child Attachment by examining its formative factors and developmental consequences through a systematic lens. Employing a systematic literature review combined with bibliometric analysis, the study synthesizes 50 peer-reviewed articles published between 2010 and 2026, following a structured PRISMA protocol and supported by VOSviewer mapping to identify thematic patterns, conceptual relationships, and research trends. The findings reveal that Attachment is a multidimensional construct shaped by the dynamic interplay between biological predispositions, psychological regulation, caregiving quality, and broader socio-relational contexts, with insecure Attachment consistently associated with adverse developmental outcomes such as emotional dysregulation, social difficulties, and increased risk of psychopathology; however, these trajectories are not deterministic, as Attachment-based interventions including parenting programs, dyadic therapies, and neurodevelopmental approaches demonstrate significant potential to improve relational quality and developmental outcomes. Nevertheless, the study critically highlights persistent gaps, particularly the fragmentation of interdisciplinary perspectives, the dominance of dyadic and Western-centric frameworks, and the limited contextualization of interventions across cultural and socio-economic settings. These findings imply the urgent need for more integrative, culturally responsive, and context-sensitive approaches that bridge theory, research, and practice to enhance the effectiveness and sustainability of Attachment-based interventions in addressing the complexities of child development in contemporary society.Attachment pada anak menjadi isu krusial dalam perkembangan sosial-emosional di tengah perubahan struktur keluarga, meningkatnya mobilitas orang tua, dan penetrasi teknologi digital yang memengaruhi kualitas interaksi anak–pengasuh. Penelitian ini bertujuan untuk mengkaji secara komprehensif faktor-faktor pembentuk Attachment serta dampaknya terhadap perkembangan anak melalui pendekatan integratif. Dengan menggunakan metode systematic literature review (SLR) terhadap 50 artikel jurnal periode 2010–2026 yang dipadukan dengan analisis bibliometrik menggunakan VOSviewer, penelitian ini memetakan tren, struktur konseptual, dan hubungan antarvariabel dalam kajian Attachment. Hasil menunjukkan bahwa Attachment terbentuk melalui interaksi kompleks antara faktor biologis, psikologis, serta dinamika relasi keluarga dan sosial, di mana pola Attachment tidak aman berkorelasi dengan peningkatan risiko gangguan psikologis, sementara intervensi berbasis Attachment memiliki potensi signifikan dalam memperbaiki kualitas relasi dan trajektori perkembangan meskipun masih menghadapi keterbatasan kontekstual dan metodologis. Temuan ini menegaskan pentingnya pendekatan multidisipliner dan kontekstual dalam memahami Attachment serta perlunya pengembangan intervensi yang tidak hanya efektif secara klinis, tetapi juga relevan secara sosial dan budaya.